An Analysis of Conversational Implicature and Humor Construction in the Podcast Conan O’Brien Needs a Friend - Isidorus Pandu Wijaya; Afriana (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
This study comprehensively investigates the phenomenon of conversational implicature within the popular podcast Conan O’Brien Needs a Friend and examines in depth its crucial role in constructing humour through dynamic and pragmatic interaction between the host and his guests. Employing a descriptive qualitative approach, the research carefully analyse a selection of podcast transcripts featuring natural conversations among Conan O’Brien and various celebrity guests, capturing spontaneous and unscripted moments of humour. The data were systematically collected through purposive sampling, with a specific focus on excerpts that exemplify the violation or deliberate flouting of Grice’s Cooperative Principle and its four conversational maxims Quantity, Quality, Relation, and Manner. The analysis is theoretically grounded in the works of (Grice, 1975), (Yule, 2005), (Brown et al., 1987), (Kotthoff, 1998), and (Mabaquiao, 2018), providing a strong foundation for understanding how implicature and speech acts interact to create humorous meaning within authentic discourse. The findings indicate humour in the podcast primarily emerges from intentional maxim violations that generate irony, exaggeration, absurdity, and incongruity, with implicatures interpreted through shared cultural assumptions and contextual understanding. Furthermore, various speech acts, including teasing, complimenting, joking, and self-deprecating humour, enrich the interaction and strengthen its overall comedic impact. This research ultimately underscores the essential function of conversational implicature in humorous discourse and significantly contributes to the broader study of pragmatics in spontaneous spoken media. The results provide valuable pedagogical insights for English language teaching, especially in developing learners’ pragmatic competence, sociolinguistic awareness, and ability to engage in authentic, natural communication.